Palliative treatment of metastatic phyllodes tumors: a case series - Ganesh, Vithusha; Lee, Justin; Wan, Bo Angela; Rakovitch, Eileen; Vesprini, Danny; Slodkowska, Elzbieta; Zeng, K. Liang; Sousa, Philomena; Yee, Caitlin; Chow, Edward (AME Case Reports, 2017)
Up to 20% of malignant phyllodes tumors (PT) metastasize, most frequently to the lungs, bone, and brain. Descriptions of metastatic PT are limited in the literature. In this series, we present three cases of malignant PT metastatic to various unusual sites including the peritoneum, soft tissue of the thigh, and scalp. All three patients initially received surgical resections, and two underwent adjuvant radiation. All three patients developed lung metastases first. Several palliative modalities were used including surgical resection, gamma-knife stereotactic radiosurgery, external beam radiation, and chemotherapy. All three patients died within 3 years of the initial diagnosis.